PENINGKATAN LITERASI MELAYU MELALUI PERTUNJUKAN SASTRA DI SRISAWAN VITHAYA SCHOOL, THAILAND SELATAN - Aulia, kaisa; puji lestari, dewi; hamdanimaula, luthfi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Improving Malay literacy through literary performances is a very good idea, so it can make students more confident in speaking Malay and broaden their understanding of what is learned. Therefore, this community service aims to improve basic Malay literacy and literary appreciation in grade 5/3 students at Srisawan Vithaya School, Southern Thailand. The method used in this community service is Participatory Action Research (PAR) which is carried out in several stages, namely problem identification, goal setting, program planning, program implementation and reflection. As a result, this program is successful in improving students' skills, especially in mastering understanding, expanding new vocabulary according to the script presented. In addition, students' confidence increases in public speaking. The success that supports this program is the enthusiasm of the students themselves. Thus, learning literature in elementary schools can improve Malay literacy and can become a new innovation and tradition that can have a positive sustainable impact at Srisawan Vithaya School, Southern Thailand.